Educational Project to Improve Problem-Based Learning in Architectural Construction Courses Using Active and Co-operative Techniques - Pons-Valladares, Oriol; González-Barroso, José M.; López-Olivares, Rafael; Arias, Iván (Revista de la Construcción. Journal of Construction, 2015)
This article presents a Project for Teaching Innovation (PTI) for the improvement of teaching practices in the Construction 1 course at the Architecture School of Barcelona (ETSAB). Since the 1980s this course has successfully made use of Problem-Basic Learning (PBL); however over the last ten years, various learning problems have arisen and become endemic. This PTI has been designed and implemented with the intention of solving this situation, and has been evaluated to determine the viability of its application. This design has been developed by the teaching team and assessed by experts from the University, which has consisted of drawing up strategies for improving each one of the identified problems. These strategies consist of incorporating new activities, and active and co-operative learning techniques. For the purposes of evaluation, indicators were designed to control the functioning of each strategy, to collect and analyse data for each indicator, and to draw conclusions. To summarise, this project has provided a means to start resolving the problems faced by the Construction 1 PBL and, at the same time, has created knowledge about the success of the techniques, activities and indicators used in this PTI which may be of use to future teaching projects.